MODERNISASI PENDIDIKAN PESANTREN BERBASIS ORGANISASI MASYARAKAT ISLAM (Studi Kasus di Pondok Pesantren Al-Falah Nagreg Bandung, Pondok Pesantren Darul Arqom Garut dan Pondok Pesantren PERSIS Tarogong Garut) - Agung, Budie; Zuhri, M.Tajudin; Ramdhani, Khalid (Jurnal Penelitian Agama, 2020)
Modernization of Islamic education cannot be separated from the rise of Muslims in modern times, Islamic thought and institutions including education (pesantren) must be modernized, ie renewed in accordance with the framework of modernity. This study aims to identify how pesantren modernization patterns are carried out in three pesantren representing Islamic mass organizations, namely Al-Falah Pesantren, Darul Arqom Pesantren and PERSIS Tarogong Pesantren, with the hope of obtaining information on similarities and differences in general patterns related to modernization pesantren education. This type of research is field research with data collection techniques such as interviews, observation and documentation. The results showed that there were similarities and differences in the pattern of modernization in Islamic mass organizations based on Islamic boarding schools.